(untitled) (Palíndromo, 2014)
This article discusses aspects of higher education in arts using Information and Communication Technologies (ICT) from a semiotic perspective. The aspects are based on the theoretical and methodological framework of Dynamic Hypermedia Devices (DHD) on the understanding that the complexity of the phenomena in question demands a complex and interdisciplinary vision able to account for the multiple dimensions that compose them. After conceptualizing the notion of DHD and its semiotic bases, it presents a case that was developed in a public university in Argentina where it was set up, in the sphere of a research project, an experience of higher education in arts through the configuration of a contextualized DHD, in response to the disciplinary specificity. Finally, we conclude that the approach is consistent for conceptualizing mediation education issues in the current physical and virtual context.